Tingkat Kesejahteraan Masyarakat Desa Himba Lestari di dalam Areal IUPHHK-HT di Kabupaten Kutai Timur, Kalimantan Timur - Jerlita Kadang Allo; Muli Edwin; Iin Sumbada Sulistyorini (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Local communities in forest management are interested parties. Investments in the forestry sector that utilize the area should be able to help regional development and improve the welfare of local communities. This study aims to understand the condition and level of community welfare in forest areas that have IUPHHK-HT. This research approach is descriptive qualitative by applying the interview method in data collection. The people in the study area are old settlers, most of whom are migrants from outside the area with low levels of education and low social status. The study area is a preparatory village that has very limited infrastructure for clean water, electricity, education, health and public infrastructure. The presence of the IUPHHK-HT company has not been able to provide welfare for the community. The level of social welfare there is still relatively low. In fact, the goal of Sustainable Forest Management (PHL) is not only sustainable production but must be able to provide economic, social and cultural benefits.Policy of fair social welfare and the spirit of agrarian reform should be able to answer economic and ecological challenges. The local community should not be used as an obstacle in the development of the timber industry in Indonesia.